Traces of Ancient Surveying in Japan - Yoshida, Kaoru (Transactions on Engineering and Computing Sciences, 2024)
Grasping the geography/topography of the land is one of the most important tasks in nation-building throughout the ages. In Ancient Izumo Province, Mt. Daisen and Mt. Sanbe were clear landmarks for the purpose. On the other hand, a large number of bronze artifacts were excavated from Shidanioku Site, Kojindani Site, and Kamo-iwakura Site in this province. These bronze artifacts were buried around the 1st century AD. If we examine the correlation using the latitude and longitude (numerical data) of landmark mountains and the bronze burial sites, we will find that Mt. Daisen, Mt. Sanbe, and the Shidanioku Site form a large isosceles triangle. It can also be seen that Mt. Daikoku and Mt. Takase, as well as Kojindani Site and Kamo-iwakura Site, which are seen as two pairs, form two isosceles triangles with a common base. They show that Ancient Izumo Province in the 1st century AD had maps for selecting burial sites and surveying techniques for making maps. There was also surveying techniques for indicating the burial sites in the field. These are the oldest surveying traces in Japan for which evidence can be shown.